Beyond K-Pop: A Discourse Analysis on ELT Research Article by Korean Authors - Lestari Yanti; Thayyib, Magfirah; Yuyun Ruqiyyat Said (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study analyzes the English research article written by Korean authors as one fruitful genre of academic discourse. It highlights how the discourse elements reflect Korean academic writing culture. This study employed a qualitative method with genre-based discourse analysis. The researchers chose one qualified research article on ELT written by Korean authors from a reputable journal. The article was analyzed in two layers: generic structure and rhetorical structure. The results showed that the writing of the Korean article uses the IMRaD as the international standard of research reports. The results also suggest that Korean academic writing places a strong emphasis on empirical evidence and formal language to ensure clarity, objectivity, and professionalism. Understanding these generic and rhetorical structures is essential for both writers and readers in the academic community, as it provides insight into how knowledge is communicated and legitimized in Korean education.